Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Motivasi Dan Kinerja Pegawai Pada Dinas Sosial Dan Pemberdayaan Masyarakat Kota Tarakan - Juliansyah, Muhammad Fuad; Kaningsih, Ana Srie; Milwan, Milwan (STKIP Singkawang, 2024)
The purpose of this study was to determine and analyze the influence of leadership and organizational culture on the motivation and performance of employees at the Department of Social and Community Empowerment of Tarakan City, either directly or indirectly. This study uses a quantitative method with a